The complete mitochondrial genome of the Anas platyrhynchos Linnaeus, 1758 breed Longshengcui and its phylogenetic analyses - Zhang, Jing-Meng; Wang, Xin; Wang, Qing-Xi; Liao, Li-Ping; Chen, Feng-Ming; Wang, Yan-Zhou; Lin, Qian; Liu, Chun-Jie; Bin, Shi-Yu (Mitochondrial DNA. Part B. Resources, 2023)
Duck breed Longshengcui ( Linnaeus, 1758 breed Longshengcui, LSC) is one of the famous native breed of the Guangxi Zhuang Nationality Autonomous Region in China. In this study, we report the complete mitochondrial genome of LSC. The mitogenome (GenBank accession no. MZ895120) has 16,602 bp in length and consisted of the well-known 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and the control region. The phylogenetic analysis showed that LSC and Zhijiang duck have highly similar genetic relationship. These results are helpful for the conservation of genetic resources and phylogeny of this species.